Power system commissioning and maintenance practice - Harker, Keith (Institution of Engineering and Technology, 1998)
Power system reliability and security is highly dependent on the practices employed in both the commissioning and maintenance processes. Both must be to a high standard to ensure that equipment does not enter service with latent deficiencies. This demands engineers who understand the necessary management involved as well as the technical processes. There is very little literature currently available on the subject; a situation which this book seeks to redress. The subject matter covers high voltage plant and the associated protection and control systems and, although it is essentially targeted at the practicalities of commissioning and maintenance, it also incorporates the underpinning technical theory and design considerations. It is aimed primarily at those who are at the outset of their career in electrical engineering, but additionally provides a thorough reference for more experienced engineers.